Impact of demographic settings on consumer perceptual response of caffeinated beverages across social cross profiles - Abeywickrema, S.; Navaratne, S.B. (University of Jaffna, 2018)
Sector of Food Science and Technology is collectively linked with Sensory Science and Consumer Behavior where the consumer’s sensitivity is concerned. This paper systematically reviews the impact of age, gender, education level, occupation, income level and expectation of the consumers toward the perceptual response for tea, coffee and a selected cola beverage. Study was conducted by a survey with a questionnaire and samples of each beverage were given to the selected respondents and tested according to ISO 5495:2005(E) standards for sensory evaluation. Collected data was analyzed for multinomial regression by SPSS 22.0 statistical software and results determines the effect of education level and occupation were insignificant (P>0.050) and age, gender, income level and expectation were significant P<0.050) towards the perceptual response. Further parameter analysis found that increment in low income levels, gender male, and younger ages with the expectation on the brand has high perception towards cola beverages while elder people, low income levels, gender female and expectation on taste has high perception on tea. Coffee shows similar results as for tea, but middle income level and expectation towards taste and quality was emphasized. Overall, the study found that pattern of consumer perception has a correlation with defined factors and the impact fluctuate consumer’s perception on beverages according to the social profile.
Keywords: Ageing; Beverages; Demographic factors; Perception